Diseño de un plan estratégico de marketing para el centro psicopedagógico “Aresim”, ubicado en el Sur del Distrito Metropolitano de Quito - Bolaños Arellano, Blanca Erika (2013)
This study focuses on the development of a strategic marketing plan for the Center Psychoeducational "ARESIM" provider of educational services and educational psychology to carry out this procedure, we conducted market research initially focused on the analysis of both environments internal and external to the organization through which it was concluded that the company has great strength in its catchment area because there are no psycho centers and similar features customers demand such services to changes undergoing education in the country, despite this strength, Psychoeducational Center "ARESIM"